Studies in the cult of Yahweh. - Smith, Morton, 1915-1991. (Religions in the Graeco-Roman World, 1995)
These two volumes collect some of the most influential and important scholarly essays by the late Morton Smith (1915-1991), for many years Professor of Ancient History at Columbia University in New York City. Smith was admired and feared for his extraordinary ability to look at familiar texts in unfamiliar ways, to re-open old questions, to pose new questions, and to demolish received truths. He practiced the \'hermeneutics of suspicion\' to devastating effect. His answers are not always convincing but his questions cannot be ignored. The essays of Volume I center on the Hebrew Bible (\'Old Testament\'), Ancient Israel and Ancient Judaism, of Volume II on the Christian Bible (\'New Testament\'), Early Christianity and Ancient Magic. Volume II also contains an assessment of Smith's scholarly achievement and a complete list of his publications.